PENGARUH DISIPLIN BELAJAR DAN UANG SAKU SISWA TERHADAP PRESTASI BELAJAR SISWA KELAS X MIA PADA MATA PELAJARAN EKONOMI DI SMA ISLAM AS-SHOFA PEKANBARU - Efendi, Salasin; Sumarno, Sumarno; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of study discipline and student allowance on the learning achievement of X MIA students on economic subjects at As-Shofa Islamic High School Pekanbaru. this research was conducted at As-Shofa Pekanbaru Islamic High School class X MIA on Economics subjects. The study was conducted in October 2018 to January 2019. This study uses a quantitative approach. The population of this study is class X MIA I and X MIA II at As-Shofa Islamic High School Pekanbaru academic year 2018/2019. The population in this study were all students of class X MIA as many as 55 students, because the population was less than 100 people, all of them were used as samples, so the sample in this study was 55 students. Data collection techniques used were questionnaires and documentation. The data analysis technique used is descriptive analysis and multiple linear regression analysis. The results of the study indicate that the learning discipline has a positive effect on student learning achievement, which is equal to 0.117. Pocket money has a negative effect on student learning achievement which is equal to 0,0007235.Keywords: Learning Discipline, Educational Pocket Money, Learning Achievement